Effect of Integrated Neem-coated Urea and Nano-urea Strategies on the Growth and Yield of Sesame (Sesamum indicum L.) - Patra, S. K.; Dolai, A. K.; Kar, Shubhadip; Mahanty, Atanu; Chakraborty, Subham; Saren, Gurupada (International Journal of Bio-resource and Stress Management, 2025)
The present field experiment was carried out during pre-kharif season (February to May) for two consecutive years of 2024 and 2025 at Baruipur Experimental Farm, University of Calcutta, West Bengal, India to evaluate the replacement potential of neem-coated prilled urea (NCPU) with nano-urea in sesame (var. Suprava, CUMS-17). The randomized block design included 10 nitrogen management treatments, combining varied proportions of soil-applied NCPU with foliar nano-urea (4% N) or 2% urea sprays. Growth, yield attributes, and seed yield were recorded and statistically analyzed. Results showed significant effects of nitrogen management on plant height, dry matter accumulation (DMA), crop growth rate (CGR, 30–60 DAS), capsules plant-¹, seeds capsule-¹, and seed yield. The highest plant height (143.71 cm), DMA (609.28 g m-2), CGR (8.28 g m-2 day-¹), capsules plant-¹ (69.47), and seed yield (1.09 t ha-¹) were achieved with 100% RDN through split NCPU application. This was statistically at par with (75% NCPU+nano-urea spray at 45 DAS; yield: 1.07 t ha-¹), suggesting that partial soil-applied N replacement with nano-urea was feasible without yield loss. The study concluded that integrating 75% RDN via NCPU with a single nano-urea spray could sustain yields comparable to full NCPU application, offering a resource-efficient, sustainable nitrogen management option for sesame in West Bengals’s pre-kharif season.